PENERAPAN MODEL PBL BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI KELAS IV SEKOLAH DASAR - Ilyas, Wandy Setiawan; Iriawan, Sandi Budi; Johani, Endang; Ershofa (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to evaluate the effectiveness of implementing the Problem-Based Learning (PBL) model assisted by sequential picture media in improving narrative writing skills among fourth-grade elementary school students. The primary issue identified was students' difficulty in developing ideas, structuring narrative compositions, and using correct spelling. The research employed Classroom Action Research (CAR) methodology using the Kemmis and McTaggart model, involving two cycles of planning, implementation, observation, and reflection. Data were collected through classroom observations, writing skill tests, interviews with students and teachers, and documentation of student work. The findings indicated a significant improvement in students' writing skills, with 65% achieving Minimum Completeness Criteria (KKTP) in Cycle 1, increasing to 88% in Cycle 2. Sequential picture media provided effective visual support to help students structure narratives, while the PBL model enhanced student engagement and critical thinking. Despite the progress, 12% of students did not meet KKTP, indicating a need for additional intervention. Overall, the combination of PBL and sequential picture media proved effective in improving narrative writing skills among students.